2022
DOI: 10.1101/2022.11.04.515237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread exposure to SARS-CoV-2 in wildlife communities

Abstract: The spillover of SARS-CoV-2 into humans has caused one of the most devastating pandemics in recorded history. Human-animal interactions have led to transmission events of SARS-CoV-2 from humans to wild and captive animals. However, many questions remain about how extensive SARS-CoV-2 exposure is in wildlife, the factors that influence wildlife transmission risk, and whether sylvatic cycles can generate novel variants with increased infectivity and virulence. We sampled 18 different wildlife species in the East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…Other wildlife or domestic species susceptible to SARS-CoV-2 infection may have contact with and facilitate transmission to WTD. Recent work in Virginia, USA, has identi ed high seroprevalence in species with shared human habitats including raccoons, squirrels, skunks, and white-footed and deer mice, in addition to viral shedding in a opossum 37 . These species could plausibly interface with humans and WTD.…”
Section: Discussionmentioning
confidence: 99%
“…Other wildlife or domestic species susceptible to SARS-CoV-2 infection may have contact with and facilitate transmission to WTD. Recent work in Virginia, USA, has identi ed high seroprevalence in species with shared human habitats including raccoons, squirrels, skunks, and white-footed and deer mice, in addition to viral shedding in a opossum 37 . These species could plausibly interface with humans and WTD.…”
Section: Discussionmentioning
confidence: 99%
“…Metatherian mammals, also known as marsupials, are an ancient group, and most marsupials are found in Australasia (around 200 species) and Central and South America (around 70 species). A study conducted by Goldberg et al found 8% of wild life Virginia opossum having detectable serum antibody against SARS-CoV-2 (37).…”
Section: Resultsmentioning
confidence: 99%
“…From a study performed in Eastern USA, 18 different wildlife species were sampled, with SARS‐CoV‐2 detected by PCR in the Virginia opossum ( Didelphis virginiana ) and equivocal detections in additional species red fox ( Vulpes vulpes ), white‐tailed deer ( Odocoileus virginianus ) Eastern grey squirrel ( Sciurus carolinensis ), Eastern cottontail rabbit ( Sylvilagus floridanus ) and bobcat ( Lynx rufus ). Species considered human commensals like squirrels and raccoons had seroprevalence ranging between 62 and71%, and sites with high human use had three times higher seroprevalence than low human‐use areas (Goldberg et al, 2022 ).…”
Section: Assessmentmentioning
confidence: 99%